KOMPETENSI LULUSAN ILMU PERPUSTAKAAN SEBAGAI PUSTAKAWAN TUNGGAL DI PERPUSTAKAAN KHUSUS (THE COMPETENCES OF LIS’S FRESHGRADUATE AS SOLO LIBRARIAN IN THE SPECIAL LIBRARY) - Febriyanto Febriyanto; Neka Rusyda Supriatna (Ikatan Pustakawan Indonesia, 2018)
The focus of this study is the competence of a librarian as a fresh graduate of Library Science, who has to manage a special library on his/her own. The purpose of this study is to identify the required competencies for graduates Library Science when they have to be a solo librarian in the special library. This research is a qualitative research using ethnography approach. The ethnographic approach is used to get the actual data that shows what is happening in the field. The result of this study indicates that the competencies which need to be developed as librarians in managing the library are the ability to build a database, develop information services, use the internet and intranet, and understand the needs of users. In conclusion, a solo librarian in a special library has competencies that adapt to user’s needs. The authors propose to improve the competence with the material, ask, and attend training in order to increase network and knowledge of librarianship.